Developing students' ideas of diversity in the ancient and modern worlds through the topic of Alexandria in the Cambridge Latin Course, Book II. Issue 37 (23rd May 2018) - Barnes, Jonathan
Abstract : My interest in undertaking a study relating to Classics and issues of diversity in the classroom is the result of several personal and circumstantial approaches to the subject, which have become more pronounced in my mind since the start of my Postgraduate Certificate of Education at the University of Cambridge.